How Does Financial Inclusion Affect Economic Growth and Income Inequality? - Annisa Zanuar Rahma; Faaza Fakhrunnas (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2022)
Financial inclusion is an important element in creating inclusive economic growth. The availability of easy access to public services can facilitate all levels of society. This study focuses on analyzing the effect of financial inclusion on economic growth and income inequality in countries based on their income categories. The research object is 440 observations with secondary data using cross-section and time-series data for 11 years, 2010 - 2020, and using objects from 40 countries in the world based on their income categories. This research uses panel method regression analysis. The results of panel data regression show that financial inclusion affects economic growth and income inequality when estimated with complementary variables, inflation, and the rule of law. In its effect on economic growth, financial inclusion has proven to be influential in the categories of lower-middle-income and high-income countries. Meanwhile, in terms of its impact on income inequality, financial inclusion is proven to affect the lower-middle-income and upper-middle-income categories of countries. The results of this study become a consideration for countries based on their income categories to increase financial inclusion so that policies can be achieved to improve people's welfare through financial inclusion